The kynurenine pathway and cognitive performance in community-dwelling older adults. The Hordaland Health Study - Solvang, Stein-Erik Hafstad; Nordrehaug, Jan Erik; Tell, Grethe S.; Nygård, Ottar; McCann, Adrian; Ueland, Per Magne; Midttun, Øivind; Meyer, Klaus; Vedeler, Christian A.; Aarsland, Dag; Refsum, Helga; Smith, A. David; et al. (Brain, behavior, and immunity, 2019)
•Tryptophan and kynurenines are related to inflammation and may be neuroactive.•Experimental studies indicates a role for the rate limiting enzyme IDO in cognition.•We assessed potential associations between kynurenines and cognition in 2174 older adults.•Lower cognitive performance is seen with higher kynurenine-to-tryptophan ratio and neopterin.•Our study supports that kynurenines may play a role in human cognition. Tryptophan, its downstream metabolites in the kynurenine pathway and neopterin have been associated with inflammation and dementia. We aimed to study the associations between plasma levels of these metabolites and cognitive function in community-dwelling, older adults. This cross-sectional study included 2174 participants aged 70–72 years of the community-based Hordaland Health Study. Tryptophan, kynurenine, neopterin and eight downstream kynurenines were measured in plasma. Kendrick Object Learning Test (KOLT), Digit Symbol Test (DST) and the Controlled Oral Word Association Test (COWAT) were all outcomes in standardized Zellner’s regression. The Wald test of a composite linear hypothesis of an association with each metabolite was adjusted by the Bonferroni method. Age, body mass index, C-reactive protein, depressive symptoms, diabetes, education, glomerular filtration rate, hypertension, previous myocardial infarction, prior stroke, pyridoxal 5′phosphate, sex and smoking were considered as potential confounders. Higher levels of the kynurenine-to-tryptophan ratio (KTR) and neopterin were significantly associated with poorer, overall cognitive performance (p < 0.002). Specifically, KTR was negatively associated with KOLT (β −0.08, p = 0.001) and COWAT (β −0.08, p = 0.001), but not with DST (β −0.03, p = 0.160). This pattern was also seen for neopterin (KOLT: β −0.07; p = 0.001; COWAT: β −0.06, p = 0.010; DST: β −0.01, p = 0.800). The associations were not confounded by the examined variables. No significant associations were found between the eight downstream kynurenines and cognition. Higher KTR and neopterin levels, biomarkers of cellular immune activation, were associated with reduced cognitive performance, implying an association between the innate immune system, memory, and language.